A Review On Cancer Vaccines - VINODH JAGANTI; SUKIRTI DAS; T.SAI SAMPATH (International Journal of Pharma and Bio Sciences, 2011)
Discovery of a potential anticancer therapy is still a challenge to the scientists. Though many different kinds of therapies are developed none of them has lived up to the task to cure cancer completely. Cancer vaccines are found to be the latest discovery in the field of cancer. Although till date only one cancer vaccine is approved by FDA, there are number of vaccines undergoing preclinical & clinical trials which are promising to be an effective anticancer therapy. This article reviews some of the basic aspects of different types of cancer vaccines along with their drawbacks & future development.